INOVASI MODEL INDEKS PENGUNGKAPAN (DISCLOSURE INDEXS) LAPORAN KEUANGAN PADA BANK SYARIAH DI INDONESIA - Siti Murtiyani (At-Tauzi : Jurnal Ekonomi Islam, 2013)
The purpose of this study is to form an index of Islamic financial report disclosure and to examine the level of disclosure of Islamic banking financial statements in Indonesia. Test the differences in level of annual financial statement disclosure. Study uses a model of the financial statement disclosure index using the Self Assessment of managers' perceptions and the method of observation of annual financial reports. Primary data of 157 Islamic bank managers in Indonesia as respondents. The results show (i) a comprehensive financial statement disclosure index can be formed, (ii) differences in the level of financial statement disclosure, based on managers' perceptions with an index of 86.01 based on annual financial disclosure reports showing index numbers of 80, 72. (iii) score disclosure index perception is an index score higher than the annual financial statement disclosure. Implication of the findings of this study is that beyond managers 'perceptions of reality, it is necessary to make efforts to increase understanding of managers' perceptions. This business can be carried out by the Central Bank and the National Sharia Board. Managers need to be adjusted to understand the disclosure of financial statements at both the individual level in Islamic banks and between Islamic banks.